Effect of N-Amide Substitution on Antioxidative Activities of Melatonin Derivatives - Panyada Panyatip; Nutjaree Pratheepawanit Johns; Aroonsri Priprem; Kouichi Nakagawa; Ploenthip Puthongking (MDPI AG, 2020)
Five N-amide substituted melatonin (MLT) derivatives were synthesized and evaluated for antioxidative activities, and compounds 9−12 showed higher electron spin resonance (ESR) response than MLT. 4-Bromobenzoyl and naphthoyl derivatives (10 and 11) presented stronger hydroxyl radical inhibitory effect than MLT in Fenton reaction. The substitution at the N1-position on the MLT core structure with acetyl (8), benzoyl (9), 4-bromobenzoyl (10), and naphthoyl (11) and N2-substitution with 4-bromobenzoyl (12) decreased the reducing power of the derivatives in ferric reducing antioxidant power (FRAP) assay. Compounds 8−11 also presented lower antioxidant capacity than their parent compound in 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) disodium salt (ABTS) assay; whereas, compound 12 presented radical scavenging activity similarly to MLT. All aryl derivatives (9−12) showed higher ability to quench peroxyl radicals than MLT about three times, especially the benzoylated derivatives (9 and 10) that presented the highest ability in oxygen radical absorbance capacity (ORAC) assay.